Shifts in Greenland interannual climate variability lead Dansgaard–Oeschger abrupt warming by hundreds of years - C. A. Brashear; T. R. Jones; V. Morris; B. H. Vaughn; W. H. G. Roberts; W. B. Skorski; A. G. Hughes; R. Nunn; S. O. Rasmussen; K. M. Cuffey; B. M. Vinther; T. Sowers; et al. (Climate of the Past)
During the Last Glacial Period (LGP), Greenland experienced approximately 30 abrupt warming phases, known as Dansgaard–Oeschger (D–O) events, followed by cooling back to baseline glacial conditions. Studies of mean climate change across warming transitions reveal indistinguishable phase offsets between shifts in temperature, dust, sea salt, accumulation, and moisture source, thus preventing a comprehensive understanding of the “anatomy” of D–O cycles (Capron et al., 2021). One aspect of abrupt change that has not been systematically assessed is how high-frequency interannual-scale climatic variability surrounding centennial-scale mean temperature changes across D–O transitions. Here, we utilize the East Greenland Ice-core Project (EGRIP) high-resolution water isotope record, a proxy for temperature and atmospheric circulation, to quantify the amplitude of 7–15-year isotopic variability for D–O events 2–13, the Younger Dryas, and the Bølling–Allerød. On average, cold stadial periods consistently exhibit greater variability than warm interstadial periods. Most notably, we often find that reductions in the amplitude of the 7–15-year band led abrupt D–O warmings by hundreds of years. Such a large phase offset between two climate parameters in a Greenland ice core has never been documented for D–O cycles. However, similar centennial lead times have been found in proxies for Norwegian Sea ice cover relative to abrupt Greenland warming (Sadatzki et al., 2020). Using HadCM3, a fully coupled general circulation model, we assess the effects of sea ice on 7–15-year temperature variability at the EGRIP. For a range of stadial and interstadial conditions, we find a strong relationship in line with our observations between colder simulated mean temperature and enhanced temperature variability at the EGRIP location. We also find a robust correlation between year-to-year North Atlantic sea ice fluctuations and the strength of interannual-scale temperature variability at EGRIP. Together, paleoclimate proxy evidence and model simulations suggest that sea ice plays a substantial role in high-frequency climate variability prior to D–O warming. This provides a clue about the anatomy of D–O events and should be the target of future sea ice model studies.